Hygienic aspects of the possibility of using the new insecticide Seller in agriculture - A, Jumaeva A; X.O, Kasimov; J, Jumaeva Z.; S, Manasova I. (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study was to identify the danger of an insecticide.Seller is 20% ks for humans and to develop, taking into account the specific features of agriculture in Central Asia, regulations that guarantee its safety in the environment and for consumers of agricultural products in hot climates.